2022
DOI: 10.5194/essd-14-845-2022
|View full text |Cite
|
Sign up to set email alerts
|

Estimating CO2 emissions for 108 000 European cities

Abstract: Abstract. City-level CO2 emissions inventories are foundational for supporting the EU's decarbonization goals. Inventories are essential for priority setting and for estimating impacts from the decarbonization transition. Here we present a new CO2 emissions inventory for all 116 572 municipal and local-government units in Europe, containing 108 000 cities at the smallest scale used. The inventory spatially disaggregates the national reported emissions, using nine spatialization methods to distribute the 167 li… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 82 publications
1
10
0
Order By: Relevance
“…The resulting r 2 = 0.94 indicates our model is strongly predictive overall of cities' self-reported emissions inventories. We further validated our predicted emissions with other studies that report emissions data for European cities, including Moran et al (2022) 15 , who estimate 2018 direct (Scope 1) emissions for more than 100,000 European cities and Nangini et al (2019) 16 , who combine self-reported inventories with other data for 343 global cities. We found fair correlation (r 2 = .50 with Moran et al, 2022; r 2 = .62 with Nangini et al, 2019) between our predicted data and these other studies (Supplementary Fig.…”
Section: Introductionsupporting
confidence: 71%
“…The resulting r 2 = 0.94 indicates our model is strongly predictive overall of cities' self-reported emissions inventories. We further validated our predicted emissions with other studies that report emissions data for European cities, including Moran et al (2022) 15 , who estimate 2018 direct (Scope 1) emissions for more than 100,000 European cities and Nangini et al (2019) 16 , who combine self-reported inventories with other data for 343 global cities. We found fair correlation (r 2 = .50 with Moran et al, 2022; r 2 = .62 with Nangini et al, 2019) between our predicted data and these other studies (Supplementary Fig.…”
Section: Introductionsupporting
confidence: 71%
“…Other inventories and data products rely on expert judgement to assign uncertainties, or uncertainties are only described qualitatively (e.g. Moran et al, 2022). Our calculation of uncertainties follows the guidelines in EEA ( 2016) and IPCC ( 2006).…”
Section: Overall Uncertaintymentioning
confidence: 99%
“…There have been a number of recent efforts to build detailed, high‐resolution bottom‐up CO 2 emissions products for urban areas and regions (e.g. Northeastern USA (ACES): Gately et al, 2015; Gately & Hutyra, 2017; China High Resolution Emission Database (CHRED): Cai et al, 2017; Cai et al, 2018; Paris, France (Origins): Lian et al, 2022; Ho Chi Minh City, Vietnam: Nguyen et al, 2021; UK NAEI: NAEI, 2013; European municipalities: Moran et al, 2022). The present study builds on one such effort, the Vulcan and Hestia CO 2 emissions products developed for North America (Gurney et al, 2009, 2012, 2020; Gurney, Liang, Patarasuk, et al, 2019; Gurney, Patarasuk, Liang, et al, 2019; Zhou & Gurney, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In 2011, UN-Habitat released a debated report indicating that urban settlements were responsible for 40% to 70% of global GHG while occupying only 2% of land. In Europe, cities take up only 4% of total land (European Environment Agency, 2019) , but the top emitter cities drive 33.4% of the total European carbon emissions Moran et al (2022). If the EU is to deliver on the European Green Deal, cities will have to be intimately involved in the climate mitigation effort.…”
Section: Cities and Networkmentioning
confidence: 99%